Studi Literatur: Dampak Stres Kerja Terhadap Kinerja Karyawan - Latif, Asrianti A.; Meyliani, Athiva; Ramadhani, Novia; Ramadani, Nindi Karya (Annusfy : Journal of Multidisciplinary Research, 2025)
Work stress is a psychological and physiological condition that arises when there is an imbalance between job demands and an individual’s ability to cope with them. This study aims to describe the concept of work stress, its causal factors, the impact it has on employee performance, and the strategies for managing it. Based on a review of recent literature (2018–2025), work stress may originate from personal factors, organizational environments, and external conditions that are interconnected. The impact of work stress is comprehensive, encompassing decreased performance, physical and mental health disorders, and disrupted social relationships in the workplace. Nevertheless, moderate levels of stress (eustress) can actually stimulate motivation and productivity. Therefore, stress management should be implemented holistically through individual, organizational, and social approaches. Organizations need to create a healthy work environment that supports employees’ psychological well-being, while individuals are encouraged to strengthen their adaptability and Emotional resilience in order to maintain optimal performance